A supply chain management model to optimise the sorting capability of a `third party logistics' distribution centre - V. S.S. Yadavalli; C. Balcou (South African Journal of Business Management, 2017)
In this paper, the process flow within a high-end 3PL distribution centre is studied in order to determine the optimal split between the parcel size categories moved within the system. The article considers the application of an optimisation (MIQP) model with a corresponding discrete event simulation model to validate the authenticity of the solution. The study assumes that the current process flow and layout of the centre remains fixed; the entering and exiting routes to and from the centre and the centre itself are located optimally within the network and the models have base times of one and seven days respectively. Performance measures have been analysed through utilization states of equipment and labour, queue contents versus time and average throughput times of each of the parcel categories. The findings in this paper can create a positive trigger for improvement within the distribution centre as equipment and labour can be downsized to decrease costs and improve safety and benefit the company through the alignment of a network of distribution centres that each applies modified relevant versions of the modelling logic conveyed in this paper.
Keywords: 650